User-Centric Privacy and Security in Biometrics - Vielhauer, Claus (Security, 2018)
The interplay of privacy, security and user-determination is an important consideration in the roll-out of biometric technologies. It brings into play requirements such as privacy of biometric data in systems, communication and databases, soft biometric profiling, biometric recognition of persons across distributed systems and in nomadic scenarios, and the convergence between user convenience, usability and authentication reliability. User-Centric Privacy and Security in Biometrics explores how developments in biometrics will address security and privacy aspects. The book surveys and evaluates how biometric techniques can enhance and increase the reliability of security strategies in a variety of applications. This includes privacy-preserving state-of-the-art works and future directions in the view of biometrics as part of broader security concepts. The fundamental emphasis is on privacy within and for biometrics, particularly for the protection of biometric data, informed consent of data usage, transparency on biometric data, and big data fraud prevention.